2013
DOI: 10.3390/ijms141019587
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MIR Genes in Response to Abiotic Stress in Hevea brasiliensis

Abstract: Increasing demand for natural rubber (NR) calls for an increase in latex yield and also an extension of rubber plantations in marginal zones. Both harvesting and abiotic stresses lead to tapping panel dryness through the production of reactive oxygen species. Many microRNAs regulated during abiotic stress modulate growth and development. The objective of this paper was to study the regulation of microRNAs in response to different types of abiotic stress and hormone treatments in Hevea. Regulation of MIR genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Negative co-regulation of miRNA expression and its target is an important step in demonstrating the post-transcriptional control mechanism. For example, in response to saline stress, cleavage of chloroplastic CuZnSOD transcripts was correlated with upregulation of miRNA398 expression in bark and in roots (Gébelin et al, 2013a), but not in leaves. This regulation was not found in relation with the other stresses tested (drought, wounding, flooding, cold, high light intensity (Gébelin et al, 2013a)).…”
Section: Discussionmentioning
confidence: 99%
“…Negative co-regulation of miRNA expression and its target is an important step in demonstrating the post-transcriptional control mechanism. For example, in response to saline stress, cleavage of chloroplastic CuZnSOD transcripts was correlated with upregulation of miRNA398 expression in bark and in roots (Gébelin et al, 2013a), but not in leaves. This regulation was not found in relation with the other stresses tested (drought, wounding, flooding, cold, high light intensity (Gébelin et al, 2013a)).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these authors showed only that cytosolic HbCuZnSOD genes had no post-transcriptional regulation by microRNA398, which could affect the expression of these transgenes ( Gébelin et al 2012 , Leclercq et al 2012 ). As regards glutathione biosynthesis, the two Hevea genes encoding the glutamyl cysteine ligase are targeted by a microRNA but not the bacterial gene ( EcGSH1 ) used in the experiment ( Gébelin et al 2013 a ). These transgenic plants accumulated three times more glutathione than wild-type plant material ( Martin et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase activity was first reported by d'Auzac et al ( d'Auzac et al 1989 ). This enzyme is encoded by a multigene family consisting of a MnSOD ( Miao and Gaynor 1993 ) and two Cu/Zn SOD s, a cytosolic isoform ( Leclercq et al 2012 ) and a chloroplastic form ( Gébelin et al 2013 a ). The MnSOD gene was first upregulated and then downregulated in latex during the first five tappings of re-opened rubber trees ( Jiyan 2011 ).…”
Section: Ros Production and Scavenging Systems In Laticifersmentioning
confidence: 99%
See 1 more Smart Citation
“…During latex regeneration, the PPP supplies NADPH for the reducing reactions in rubber biosynthesis, and supplies pentose for nucleic acid synthesis ( Lynen, 1969 ). Various environmental factors such as cold, wind, disease, and especially wounding stresses from tapping affect rubber yield ( Sookmark et al, 2002 ; Venkatachalam et al, 2009 ; Li et al, 2010 ; Gebelin et al, 2013 ; Long et al, 2015 ). The act of tapping the tree inevitably imposes a form of wounding stress that leads to peroxide accumulation in latex.…”
Section: Introductionmentioning
confidence: 99%